Artificial Intelligence-Based Application Cake as the Alternative for Learning Speaking: Opportunities and Challenges - Suciati Suciati; Abdurrahman Faridi; Januarius Mujiyanto; Yudhi Arifani (Universitas Negeri Semarang, 2022)
Technology in education develops so fast. Learning language also needs media that can support the students to develop their speaking skill. This article aims to analyze the opportunities and challenges of students in using artificial intelligence-based application Cake as the alternative for learning speaking. In this qualitative research, the writer used observation, interview and documentation. It was conducted on the second semester students of Tadris Bahasa Inggris study program, Tarbiyah Faculty of Institut Agama Islam Negeri Kudus. The results showed that Cake application is so helpful and contributive to the students’ learning process because this application is easy to access, serves various topics in every level and category, the examples of conversation, chance for practicing to speak, evaluations of pronunciation, score of pronunciation/speaking and repetition. The challenges for the students in using this application are the materials unavailability, internet connection, gadget capacity and finding appropriate place for accessing and learning it. This application records and test the students’ speaking so it needs a quiet place.